Investigation of Association with First-Trimester Free Human Chorionic Gonadotropin-ß, Pregnancy - Associated Plasma Protein-A, and Adverse Pregnancy Outcomes - Gonen, Gokhan; Kemal Akpak, Yasam; Muhcu, Murat (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVES: This study aimed to investigate the association between first-trimester screening maternal serum markers (free human chorionic gonadotropin-beta (β-hCG), pregnancy-associated plasma protein-A, and adverse pregnancy outcomes (gestational hypertension, preeclampsia, preterm delivery, intrauterine growth restriction, oligohydramnios, intrauterine ex-fetus, abruptio placentae, and gestational diabetes mellitus). STUDY DESIGN: This was a retrospective cohort study including 1516 women who delivered a singleton pregnancy at GATA Haydarpasa Education Hospital from 2006 to 2009. Patients with multiple pregnancies, chromosome aberrations, or fetal anomalies were excluded. Extreme values of corrected- pregnancy-associated plasma protein-A and free β-hCG, and their association with adverse pregnancy outcomes were analyzed. RESULTS: Adverse pregnancy outcomes at the cutoff level of ≤0.25 c-pregnancy-associated plasma protein-A MOM values positive likelihood ratio (+LR) was 7.5 (95%CI 2.426-19.836) and had a significant correlation (r=0.108, p<0.01). It was also a significant correlation with adverse pregnancy outcomes (r=0.189, p<0.01) at the cut-off level of ≤0.50 corrected-pregnancy-associated plasma protein-A MOM values and the +LR was 2.388 (95%CI 1.889-2.991). Association between low corrected-pregnancy-associated plasma protein-A MOM values and adverse pregnancy outcomes were statistically significant and had a poor association (AUC, 0.630 95%CI 0.596-0.663, p<0.01). Preeclampsia was statistically significant, however had a fair association (AUC, 0.74 95% CI 0.690-0.802, p<0.01). Preterm birth was statistically significant but had a poor association (AUC, 0.568 95% CI 0.512-0.624, p<0.05). CONCLUSION: First-trimester maternal serum low pregnancy-associated plasma protein-A values are significantly associated with adverse pregnancy outcomes. It may be a useful tool to predictive not only chromosome anomalies but also adverse pregnancy outcomes.